Efeito da fotobiomodulação a laser sobre a viabilidade de fibroblastos expostos a medicamentos endodônticos - Lima, Gustavo Danilo Nascimento (2015)
In endodontics, to promote the elimination of microorganisms that resisted the preparation step of the canal, it becomes important to use of intracanal medications. However, the degradation products of these materials when in contact with the periapical region can cause chemical irritation and inflammation, leading to a delay in the healing process. The association with laser photobiomodulation (FTL) has been proposed as a strategy to minimize this problem. Thus, the aim of this in vitro study was to evaluate the association between the laser photobiomodulation (FTL) and intracanal medications on the viability of fibroblasts in different exposure times. For the cytotoxic test was established culture with 3T3 fibroblasts cell density of 2x104 cells / well in 96 well plates. Two medications and divided into experimental groups were used: calcium hydroxide - distilled water (HC), iodoform - distilled water (IO) and control group with cells and culture medium (CTR), with or without laser photobiomodulation. Eluates of endodontic medications were prepared and placed in contact with the cells for periods of 24, 48 and 72 hours. In relation to laser irradiation were two sessions with an interval of 6 hours, with AlGaInP laser emitting radiation 660nm, 10mW of power density, energy density of 3 J / cm² for 12 s per well. After each experimental time, the colorimetric assay was executed using the metiltetrazólio reagent (MTT). The reading of the plates was performed at the spectrophotometer, using the optical density at 540 nm. Statistical analysis was applied 3-way ANOVA followed by Tukey test. In the results the triple interaction was not significant (P = 0.053), but all double interactions were laser x medication (P = 0.002); Laser x time (P <0.001); and medication x time (P <0.001). The CRT when irradiated, was different from the non-irradiated with a higher cell viability rate. Independent of use of FTL, the control had higher cell viability and HC smaller, presenting itself as the most cytotoxic. At 24h, the use of lasers reduced cell viability, whereas the opposite was observed in the evaluation of 72h. An increase in the cytotoxicity of endodontic medications was observed with the passage of time. It was concluded that all tested medications are cytotoxic promoting a decrease in cell viability over the experimental periods, and when associated with FTL, was promoted increased cell viability for 72 hours.